Ayat Al-Qur’an mengenai hak asasi manusia: Kajian analisis terhadap pentafsiran golongan Muslim Liberal di Indonesia / Edward Maofur - Edward, Maofur (2017)
The belief that the application of human rights is the standard measurement for the success or decay of any living society is inaccurate unless that standard has been assessed and one finds it convincing. A Muslim should deeply believe more in the al- Qurʼan which possesses its own concept of human rights compared to other humanly formulated conceptions of human rights. With this, assertions of human rightsʼ violations are normally untrue if its conception is contrary to the Qurʼanic conception of what constitutes human rights. This research seeks to identify the Qur’anic concept of human rights and its interpretation by the Indonesian Liberal Muslim community, especially regarding the issue of gender equality and religious freedom as example. This interpretation is then compared and contrasted against the views of Qur’anic interpreters. The research adopts inductive-analysis and comparative methods to ensure whether the method of interpretation applied by this community complies with the established standards for interpreting the Qur’an. The study has discovered that the interpretation of the Indonesian Liberal Muslim community is western oriented. This is due to western liberalism strongly influencing their understanding of the al-Qur’an’s conception of human rights. This group then draws on their erroneous interpretation of the al-Qur’an to justify their existing opinions on human rights.